The Teaching Practicum Experience of Pre-service English Language Teachers through Synchronous Learning - Nurjannah Nurjannah; Sri Lestari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
During the pandemic COVID-19, teaching practicum has shifted from offline to online mode following the school policy. In this demanding situation, pre-service teachers might have new experience of conducting online teaching learning activities. The experience could be found in planning, teaching, and reflecting stages of teaching practicum. This study employed two pre-service English language teachers who majored in the English Language Education narrating their experience of their teaching practicum. The data was obtained from the pre-service teachers’ reflective journals and interviews. The findings of this study showed various experiences of teaching English in synchronous online classes, including the experience of using the platform, the experience with the students, the experience of teaching English lessons, and the experience with cooperating teacher.